Cu(OTf)(2)-catalyzed alpha-halogenation of ketones with 1,3-dichloro-5,5 `-dimethylhydantoin and N-bromosuccinimide - Jagdale, Arun R.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2009)
Copper(II) triflate catalyses efficiently the alpha-halogentation of aryl or alkyl ketones with 1,3-dichloro-5,5'-dimethyl-hydantoin and N-bromosaccinimde to give the corresponding alpha,alpha-dichloroketones and alpha-bromoketones in high yield with excellent product selectivity.
Keywords: Bromination; Catalyst; chlorination; copper (II); Ketone; Lewis acid